Protocols for evaluating resistance to leaf and stem rusts in durum and bread wheats - S.V. SAI PRASAD; H.N. PANDEY, A.N. MISHRA*, G.S. SHIRSEKAR, S.R. YADAV , V.G. DUBEY, K. KAUSHAL, (Indian Phytopathology, 2009)
Leaf rust pathotypes- 12-5 (29R45), 162-2 (93R39), 12-2 (1R5), 104-2 (21R55), 162-3 (29R7), 11 (0R8) and 106 (0R9), and stem rust pathotypes- 117-6 (37G19), 117A (38G2), 117-1 (166G2), 117A-1 (38G18) and 117-3 (167G3) were found appropriate for evaluating resistance in durum wheat; while leaf rust pathotypes- 77-6 (121R55-1), 77-5 (121R63-1), 77-7 (121R127), 77-2 (109R31-1) and 77-1 (109R63), and stem rust pathotypes- 40A (62G29), 40-1 (62G29-1), 295 (7G43), 11 (79G31) and 117-4 (166G3) need to be used for evaluating resistance in bread wheat, based on their respective high degrees of virulence on the two wheat species. Durum wheat genotypes- Local Red, Local Yellow, Karnataka Local, SV 683-B, A 28, GW 1, Chadur Biswa 7, A 206, Malvi Local and Bansi Local; and bread wheat varieties Pissi Local and Dhar Local, being susceptible to the aforesaid pathotypes with high AUDPC values, are suitable for rapid multiplication of the appropriate rust inoculum to ensure effective screening for rust resistance in both durum and bread wheats. These protocols for rust resistance breeding should further strengthen the ongoing wheat crop improvement programme of the country.